ANESTHETIC MANAGEMENT OF A SHORT UROLOGICAL PROCEDURE IN A PATIENT WITH MULTISYSTEM ATROPHY - CEREBELLAR TYPE: A CASE REPORT - NAGELLA, AMRUTHA BINDU; AKRAM, VASIM; AK, AKSHAYA; MS, RANJITHA; SUBBANNA, SHASHIDHAR; PARTHASARATHY, PRABHA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Multisystem atrophy cerebellar type (MSA-C) is a rare, fatal, and progressive neurological disorder characterized by features of atypical parkinsonism and autonomic dysfunction. This condition poses numerous challenges in the perioperative period to the anesthesiologist for the safe conduct of anesthesia. Here, we report a case of 65-year-old male patient with the diagnosis of MSA-C who was posted for a short urological procedure. General anesthesia is usually preferred for MSA-C patients due to the autonomic dysfunction. However, after considering the risks of general anesthesia in MSA-C, we administered a low-dose spinal anesthetic. The patient was hemodynamically throughout the surgery and the post-operative period was uneventful.